Sociodemographic Analysis of Suicide Rates Among Older Adults Living in Ecuador: 1997–2019 - Troya, M. Isabela; Gerstner, Rebekka M.; Narvaez, Freddy; Arensman, Ella (Frontiers in Public Health, 2021)
Background Despite most suicides occurring in Low-and-Middle-Income-Countries,limited reports suicide rates in older adults among LAMICs.In Ecuador, high suicide rates have been reported among adolescents.Little is known about the epidemiology of suicides among older adults in Ecuador. Aim To examine the sociodemographic characteristics of suicides among older adults living in Ecuador from 1997-2019. Methods Observational cross-sectional study using Ecuador’s National Institute of Census and Statistics database from 1997-2019 in Ecuadorians aged 60 and older.ICD-10(X60-X84) reported suicide deaths were included in addition to deaths of events of undetermined intent(Y21-Y33).Sex, age, ethnicity, educational level, and method of suicide were analysed.Annual suicide rates were calculated per 100,000 by age, sex, and method.To examine trends in rates of suicide, Joinpoint analysis using Poisson loglinear regression was used. Results Suicide rates of female older adults remained relatively stable between 1997-2019 with an average annual percentage increase of 2.4%, while male rates increased and maintained relatively stable within the last three years (2017-2019).The annual age-adjusted male suicide rate was 29.8 per 100,000, while the female suicide rate was 5.26 per 100,000. When adding deaths of undetermined intent, the annual male rate was 60.5 per 100,000, while the same rate was 14.3 for females.Highest suicide numbers were reported in urban districts, males, and those with lower education status. Conclusion This study contributes to building the baseline for further studies on suicide rates of older adults in Ecuador.Results highlight priority areas of suicide prevention.By examining suicide trends over a 23-year period, findings can help inform policy.